Bio-agronomic efficiency indices of eggplant and tomato intercropping - Filho, Arthur B Cecílio [UNESP]; Machado, Beliza QV [UNESP]; Alves, Anarlete U.; Pereira, Breno de J. [UNESP]; Guerra, Natan M.; Bezerra Neto, Francisco (FapUNIFESP (SciELO), 2022)
The successful intercropping with vegetables depends on the type of crops grown and on the proper handling of tested treatments, such as the time of transplanting a crop in relation to transplanting another crop, among others. Thus, the objective of this work was to evaluate the bio-agronomic performance of eggplant and tomato for industry, in intercropping, in relation to their single crops, as a function of the transplanting time of the eggplant in relation to the tomato and of the cultivation season (summer or winter). The experimental design used was a randomized complete block with ten treatments and four replications, implanted in two growing seasons (from February to September and from August to February), where the treatments consisted of ten eggplant transplanting times (-30,-25,-20,-15,-10,-5, 0, +5, +10 and +15 days in relation to tomato transplantation). In each block, plots of eggplant monocultures were planted in each transplanting time, as well as a plot in tomato monoculture in order to obtain the bio-agronomic indices. The competition and bio-agronomic efficiency indices of the crops and of the intercropped systems were evaluated. The variation in the transplanting time of eggplant in relation to tomato significantly interferes in the bio-agronomic performance of both species. Eggplant transplanting performed between-20 and-15 days compared to tomato transplantation reduces the dominance of one crop over the other and the interspecific competition for environmental resources. The intercropped system has greater land equivalent ratio when the eggplant is transplanted at +15 days after transplanting the tomato.
Índices de eficiência bio-agronômica do consórcio de berinjela e tomate
Keywords: crop sowing times; intercropping system; Solanum lycopersicum; Solanum melongena